Efektivitas Penggunaan E-Modul untuk Meningkatkan Kinerja Siswa dalam Praktik Kerja Industri - Pratiwi, Fitri (Universitas Tanjungpura, 2024)
This study aims to assess the effectiveness of a module in enhancing the performance of vocational high school (SMK) students during their Industrial Work Practice (Prakerin), enabling students of SMK Pancasila Kubu Raya to acquire job skills that meet the demands of the business world (DU) or the industrial sector (DI). The research adopts a qualitative approach with a descriptive research design. The type of study utilized is a library study. The subjects of this research are students from SMK Pancasila Kubu Raya who have participated in the Prakerin program. Data collection involved observation and in-depth interviews with students and teachers. The researchers conducted direct observations of the study subjects. The implementation of the Industrial Work Practice program (Prakerin) lasted for three months. SMK Pancasila offers two major programs: Motorcycle Business Engineering (TBSM) and Office Automation and Governance (OTKP). The findings indicate that the Prakerin module applied at SMK Pancasila Kubu Raya is effective in enhancing students' job skills. The use of the module during the Industrial Work Practice (PRAKERIN) effectively improves students' understanding of the concepts and materials applied during Prakerin. However, the module requires improvements to provide a clear foundation that aids students in applying theory to real-life situations during Prakerin. The Prakerin experience enhances students' comprehension of materials related to industrial work practices. To ensure that Prakerin activities align with objectives, students must be adequately prepared prior to starting their Prakerin. Although teachers monitor students before and during the Prakerin program, further preparations are necessary